Vitamin B12 absorption–a study of intraluminal events in control subjects and patients with tropical sprue. Issue 12 (December 1975) - Kapadia, C R; Bhat, P; Jacob, E; Baker, S J
Abstract : The intraluminal fate of orally administered radioactive vitamin B12 has been studied in control subjects with normal vitamin B12 absorption and those with vitamin B12 malabsorption due to tropical sprue. In control subjects 1 to 21% of the dose was bound to sedimentable material and 37 to 75% was bound to immunoreactive intrinsic factor. In subjects with vitamin B12 malabsorption due to tropical sprue, the results were identical with the control subjects. Bacteriological studies showed a statistically significant correlation between both the number of flora in the jejunum and the number of bacteroides in both the jejunum and ileum and vitamin B12 malabsorption. In patients with tropical sprue who have normal intrinsic factor secretion, the vitamin B12 absorptive defect is not due to binding of the vitamin to bacteria or to alteration to the intrinsic factor vitamin B12 complex in the intestinal lumen. The lesion appears to be one of the mucosal cell receptors or of the cells themselves, possibly caused by bacterial toxins.